1998
DOI: 10.1111/j.1532-950x.1998.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral Subluxation of Hip Joints in Dogs Measured in a Weight‐Bearing Position With Radiography and Computed Tomography

Abstract: The DLS test can be performed with CT or routine radiography to measure variable amounts of DLS in weight-bearing hip joints oriented similarly to those of a standing dog. After additional long-term follow-up studies evaluating the development of OA and breed effects are performed, the DLS method may prove useful in studies of normal and abnormal hip joint development related to canine hip dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
2
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(164 citation statements)
references
References 6 publications
4
133
2
10
Order By: Relevance
“…Passive hip laxity (PHL) is the primary risk factor for the development of degenerative joint disease in dogs with hip dysplasia (Smith et al, 1995), and has been the support of research in new radiographic diagnostic techniques (Smith et al, 1990;Farese et al, 1998;Flückiger et al, 1999;Vezzoni et al, 2005). The most widely known, very well investigated and accepted technique for PHL measurement in dogs is a stress-radiographic method, denominated PennHIP (Ginja et al, 2006).…”
mentioning
confidence: 99%
“…Passive hip laxity (PHL) is the primary risk factor for the development of degenerative joint disease in dogs with hip dysplasia (Smith et al, 1995), and has been the support of research in new radiographic diagnostic techniques (Smith et al, 1990;Farese et al, 1998;Flückiger et al, 1999;Vezzoni et al, 2005). The most widely known, very well investigated and accepted technique for PHL measurement in dogs is a stress-radiographic method, denominated PennHIP (Ginja et al, 2006).…”
mentioning
confidence: 99%
“…Thirty-two adult German shepherd dogs that were either normal (8) or with hind-limb lameness (24) were used. Nine-teen were females and 13 males.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative measures of passive hip joint laxity such as the Norberg angle and distractive index derived from newer stress-radiographic diagnostic methods are also often used 4,22,23 . More recent diagnostic techniques include a dorsolateral subluxation test using radiography 7,8,16,17 , dynamic ultra-sonography 1 , computed tomography 8 and morphometric assessment of the canine hip joint using the dorsal acetabular rim view and the centre-edge angle 19 . A semiquantitative radiographic method of postoperative evaluation of traumatic hip dislocation was described in dogs 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since in this method, dogs under general anesthesia are held in the standing position without excessive extension or flexion of the hindlimbs on the imaging platform, abnormal tensioning or twisting is not induced in the joint capsule. Therefore, the degree of joint laxity between the femoral head and acetabulum can be accurately evaluated [4,9,14]. Although further studies may be necessary to fully understand the phenomena observed in this study, they might be due to the formation of joint-supporting tissues such as periarticular fibrosis and the reinforcement of the supporting tissues around the hip joint with growing.…”
mentioning
confidence: 86%
“…Computed tomography (CT) scan was performed under the position according to the procedure previously reported with a minor modification [4,9,14]. The dogs under isoflurane anesthesia were positioned on a laboratory-made platform in ventral recumbency.…”
mentioning
confidence: 99%